Semidefinite Relaxation Method for Target Localization by MIMO Radar Using Bistatic Ranges - Bin Sun; Haowen Chen; Xizhang Wei; Xiang Li (International Journal of Distributed Sensor Networks)
We address the target localization problem by using bistatic range (BR) measurements in widely separated multiple-input multiple-output (MIMO) radar network. The BR information defines a set of elliptic equations from which the target location can be estimated. By applying the semidefinite relaxation (SDR), we transform the nonconvex BR-based localization problem into a convex semidefinite programming (SDP) problem, whose solution is guaranteed to be globally optimal without initial estimate. Moreover, we extend this method to robustly solve the localization problem in the presence of antenna position errors. Simulation results demonstrate that the proposed SDR method provides superior estimation performance over the existing method.